Dobra zmiana jest możliwa, czyli podejście doceniające w bibliotece = Good change is possible - an appreciation approach in libraries - Banaszewski, Kamil; Bartosiak, Katarzyna (Zielona Góra: "Pro Libris" Wydawnictwo Wojewódzkiej i Miejskiej Biblioteki Publicznej w Zielonej Górze)
Making changes to an organization to improve it and adapt it to the new demands of the outside world is a task faced also by libraries. Innovations and transformations are quite a challenge, because employees often come to them with distrust, and react to them with stress and reluctance. Searching for missing elements and problems and diagnosing areas where something does not work as it should is characteristic of a traditional approach to development and organizational change. An alternative to this view of transformation in the workplace could be an appreciation approach where the process of change should be initiated and based on the positive recognition and selection of what is best in the company's past performance. The authors give an overview of the concept of the appreciation approach developed by D. Cooperrider, discuss its genesis, the main principles and, most importantly, its methodology, known as the 4D model (Discovery, Dream, Design, Destiny), which is used, amongst other things, for the SOAR analysis. Using the examples of foreign libraries, the authors point out the possibility of using the appreciation approach for facilitating the transformation of libraries into learning organizations, as a tool to measure the level of library services, as well as a technique to help to redefine jobs and roles, and transform organizational structures.
Keywords: biblioteki; Dociekanie Doceniające; organizacje; zmiana; Cooperrider, David; libraries; Appreciative Inquiry; organizations; change